An effective approach to improve split-gate flash product data retention. (October 2017) - Wei, Dailong; Cao, Zigui; Tang, Zhilin
Abstract: Data retention is one of the most important reliability characteristics of split-gate flash. Therefore, many efforts were made to improve data retention of split-gate flash. By experiments, it was found that higher chlorine concentration produced in FGSP2 oxide deposition can induce worse data retention. Thus, reducing chlorine concentration is an effective approach to improve data retention for split-gate flash product. Additional RTO annealing between FGSP2 oxide deposition and FGSP2 etching could reduce chlorine concentration, and improve FGSP2 oxide film quality, and then get better data retention.